Beyond the γ-aminobutyric acid hypothesis of schizophrenia - Fujihara, Kazuyuki (Frontiers in Cellular Neuroscience, 2023)
Abnormalities in the γ-aminobutyric acid (GABA) system have been reported in the postmortem brains of individuals with schizophrenia. In particular, the reduction of one of the GABA-synthesizing enzymes, the 67-kDa isoform of glutamate decarboxylase (GAD67), has garnered interest among researchers because of its role in the formation of γ-oscillations and its potential involvement in the cognitive dysfunction observed in schizophrenia. Although several animal models have been generated to simulate the alterations observed in postmortem brain studies, they exhibit inconsistent behavioral phenotypes, leading to conflicting views regarding their contributions to the pathogenesis and manifestation of schizophrenia symptoms. For instance, GAD67 knockout rats (also known as Gad1 knockout rats) exhibit marked impairments in spatial working memory, but other model animals do not. In this review, we summarize the phenotypic attributes of these animal models and contemplate the potential for secondary modifications that may arise from the disruption of the GABAergic nervous system.